Charles Nettleton, Laws of the State of New-Jersey, at 370-71, An Act respecting slaves, § 9 (1821) - (:unkn) unknown (General Publisher, 1798)
Prohibited “any negro or other slave” from hunting or carrying a gun on the first day of the week, or Sunday subject to imprisonment.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES